A comparison of case definitions for infant atopic dermatitis in a multicenter prospective cohort study. Issue 3 (12th July 2021) - Zheng, David X.; Geller, Ruth J.; Robinson, Lacey B.; Boos, Markus D.; Camargo, Carlos A.
Abstract : This study identified two infant AD case definitions that were strongly associated with known AD risk factors. These case definitions can be used to study novel AD risk factors in large cohort studies, potentially providing new insights into the epidemiology of infant AD.